2012
DOI: 10.1007/s10158-012-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-sensitive chloride ion channels in Anopheles gambiae Sua-1B cells

Abstract: In this study, we performed electrophysiological analysis of Anopheles gambiae Sua-1B cells having "neuron-like" morphologies using the patch clamp method. The recorded cells (n = 79) had processes resembling axons/dendrites, with 63 % unipolar, 22 % bipolar, and 15 % multipolar. While no inward currents were observed following step depolarizations (holding potential = -80 mV), a slowly activating outward current was observed in 96 % of the cells, especially at depolarized potentials. The amplitude of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…When characterizing the chloride channels present in Sua1B cells, this study found the majority of channels to be VSCCs, while those Diykov et al [7] found were predominantly the CACC channel subtype. Both chloride channel subtypes were found in each study, but are thought to activate in different physiological circumstances and occur independently of one another.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…When characterizing the chloride channels present in Sua1B cells, this study found the majority of channels to be VSCCs, while those Diykov et al [7] found were predominantly the CACC channel subtype. Both chloride channel subtypes were found in each study, but are thought to activate in different physiological circumstances and occur independently of one another.…”
Section: Discussionmentioning
confidence: 56%
“…Outwardly rectifying voltage sensitive currents observed in native Sua1B cells seem to be mediated either primarily by CACCs or by a combination of CACCs and volume-sensitive, outwardly-rectifying anion channels [7]. High concentrations of lindane, an organochlorine insecticide, inhibited growth of Sua1B cells, but the response did not occur in a typical concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…There have been a number of studies in which cultured insect cells have been treated with the molting hormone 20‐hydroxy ecdysone (20‐OH E) and which have resulted in a more spindly shape as the cells differentiate into neuron‐like structures with longer processes. In some cases, it appears that voltage‐gated sodium, calcium, potassium or chloride channels have been induced concomitant with the morphological change 37–41 . More recently, it has been shown that 20‐OH E treatment of Aedes RML12 cells led to spontaneous neuroactivity as monitored by multiwell microelectrode array, and that this could be enhanced by treatment with the GABA antagonist gabazine and especially nicotine 42 …”
Section: Lab‐on‐a‐chip or Organ‐on‐a‐chip Technologies For Insecticide Screening Or Mode Of Action Studiesmentioning
confidence: 99%